Relationship Of Mother's Knowledge About Protein Energy Malnutrition With Nutritional Status Of Preschool Children In Kristina Clinic Perumnas Sidikalang In 2021 - Desriati Sinaga; Aprilita Sitepu; Meliana Sianturi (Institute of Computer Science (IOCS), 2021)
Protein Energy Malnutrition (PEM) is one of the important nutritional disorders in Indonesia and other developing countries. One of the highest prevalence is found in children under five, one of which is caused by mother's knowledge. The purpose of this study was to analyze the relationship between mother's knowledge about protein energy malnutrition and the nutritional status of preschool children at the Clinic. The sample in this study were all mothers who had preschool-aged children who came to visit Kristina Clinic Perumnas Sidikalang in 2021 as many as 32 people. The results showed that the majority of respondents had good knowledge and the nutritional status of children was within normal limits, and there was a relationship between mother's knowledge of protein energy malnutrition and the nutritional status of preschool children with p = 0.001. The higher the mother's knowledge, the higher the child's nutritional status will be.